IoT dalam Penyebaran Informasi Merk Kopi Si Pahit Lidah Besemah Menggunakan Metode Design Thinking 101 - Nurmaleni (Jurnal Informatika Ekonomi Bisnis, 2021)
IoT (Internet of Things) is a concept that has a function to expand connectivity on the Internet that is connected continuously. Internet of Things is also said to be a global network infrastructure, which can connect hardware and virtual through the exploitation of data capture and communication capabilities. A virtual device that is more common and easy to use is the Design Thinking 101 method. Introducing the general public as well as the surrounding community, especially Besemah, about the Si Pahit Lidah Besemah coffee brand through the virtual world. Design Thinking 101 is a design methodology that is useful in solving complex problems by understanding the human needs involved. Furthermore, design thinking will be processed through the Parallax web program. The processing stages are Empathize, Define, Ideate, Prototype and Test. Design Thinking results from the processed stages which are then collaborated to form an effective virtual appearance. Followed by IoT. The results of the use of this method in the form of the operation of the Si Pahit Lidah Besemah coffee brand information are conveyed well and interestingly with website. The result of Design Thinking has conveyed information well and is interesting. Although the level of access to the internet also has a limit on quotas, it can be recommended to help this coffee brand improve its accuracy to convey information accurately, well and attractively.